Pengaruh Penggunaan Model Example-Non Example Terhadap Keterampilan Menulis Teks Prosedur Siswa Kelas XI SMAN 16 Padang - Seska Oktari; Sri Hartati, Yulia; Nisja, Indriani (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
The purpose of this study was to describe the effect of using the example non-example model on the procedural text writing skills of class XI students of SMA Negeri 16 Padang. This type of research is quantitative research. The method used is the experimental method. The research design used is the One Group Pretest-Posttest Design. The population of this research is class XI students of SMA Negeri 16 Padang for the 2022/2023 academic year. The sample in this research is class XI MIPA 3. The independent variable is the example non-example model, while the dependent variable is writing procedure text. The instrument used in this study was a performance test, namely a performance test for writing procedural texts. Data collection in this research was carried out in three meetings, pre-test, treatment and post-test. The results of this study are that H1 is accepted and H0 is rejected. Thus the use of the Example Non Example model affects the skills of writing procedure texts for class XI students of SMA Negeri 16 Padang.